How Adhesion Molecule Patterns Change While Neutrophils Traffic through the Lung during Inflammation - Franziska M. Konrad; Julia Wohlert; Jutta Gamper-Tsigaras; Kristian-Christos Ngamsri; Jörg Reutershan (Mediators of Inflammation)
In acute pulmonary inflammation, polymorphonuclear cells (PMNs) pass a transendothelial barrier from the circulation into the lung interstitium followed by a transepithelial migration into the alveolar space. These migration steps are regulated differentially by a concept of adhesion molecules and remain—despite decades of research—incompletely understood. Current knowledge of changes in the expression pattern of adhesion molecules mainly derives from in vitro studies or from studies in extrapulmonary organ systems, where regulation of adhesion molecules differs significantly. In a murine model of lung inflammation, we determined the expression pattern of nine relevant neutrophilic adhesion molecules on their way through the different compartments of the lung. We used a flow cytometry-based technique that allowed describing spatial distribution of the adhesion molecules expressed on PMNs during their migration through the lung in detail. For example, the highest expression of CD29 was found in the intravascular compartment, highlighting its impact on the initial adhesion to the endothelium. CD47 showed its peak of expression on the later phase of transendothelial migration, whereas CD11b and CD54 expression peaked interstitial. A pivotal role for transepithelial migration was found for the adhesion molecule CD172a. Thereby, expression may correlate with functional impact for specific migration steps. In vitro studies further confirmed our in vivo findings. In conclusion, we are the first to determine the changes in expression patterns of relevant adhesion molecules on their migration through the different compartments of the lung. These findings may help to further understand the regulation of neutrophil trafficking in the lung.